Experimental study of impact of anisotropy and heterogeneity on gas flow in coal. Part I: Diffusion and adsorption. (15th November 2018) - Tan, Yuling; Pan, Zhejun; Liu, Jishan; Kang, Jianhong; Zhou, Fubao; Connell, Luke D.; Yang, Yunxia
Abstract: Gas is adsorbed in the pores of coal matrix and during gas production gas is desorbed from the pore surface and diffuses through the matrix pore structure and flows in the fracture/cleat system to the production well or boreholes. However, coal is highly heterogeneous and anisotropic. How heterogeneity and anisotropy affect the gas storage and especially the diffusion behaviour is not well studied. In this work, a series of measurements were performed on three dry cubic coal samples cut from the same coal block from the Bowen Basin, Australia, using an adsorbing gas, methane. For each sample, gas adsorption experiments with gas flowing from three principal directions were performed. The diffusion data was fitted with a bidisperse diffusion model to obtain diffusion coefficient. The three samples, although from the same coal block, showed difference in adsorption amount and significant difference in effective diffusivity. It was found that the effective macropore diffusivity increased with gas pressure and effective micropore coefficient decreased with gas pressure. The effective diffusivity showed difference among samples and directions, demonstrating coal heterogeneity and anisotropy both have a significant impact on gas diffusion behaviour. However, no generalisation can be obtained with any single pore structure parameter, such as pore size or surface area, as it may be related to all pore and fracture structures at various scales.